Understanding Proto-Insurgencies RAND Counterinsurgency StudyÑPaper 3 - Byman, Daniel (RAND Corporation, 2007)
This study examines how terrorist groups transition to insurgencies and identifies ways to combat proto-insurgents. It describes the steps groups must take to gain the size and capabilities of insurgencies, the role of outside state support, and actions governments can take to prevent potential insurgencies from blossoming. The most effective U.S. counterinsurgency action would be to anticipate the possibility of insurgencies developing; it could then provide training and advisory programs and inhibit outsides support.